1988
DOI: 10.1007/bf01794679
|View full text |Cite
|
Sign up to set email alerts
|

Orbital cavernous hemangiomas

Abstract: Cavernous hemangiomas are the most frequently found primary tumors in the orbital region. They normally appear in adults. Diagnostic features in the majority of cases include protrusio bulbi and orbital enlargement. B-Scan and computed tomography/MRI are the prime diagnostic aids. We recommend surgical removal of these tumors, at least in cases with marked orbital protrusion or significant optic nerve compression. The prognosis is usually good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In the orbit, they represent 80% of adult angiomatous malformations, accounting for 9.5% to 15% of primary orbital expanding masses [1,5]. Orbital cavernomas have been reported to appear with symptoms at an average age of 42 years, ranging from 18 to 67 years [6]. Intracranial and orbital cavernous hemangiomas in children, especially in infants, are rare [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the orbit, they represent 80% of adult angiomatous malformations, accounting for 9.5% to 15% of primary orbital expanding masses [1,5]. Orbital cavernomas have been reported to appear with symptoms at an average age of 42 years, ranging from 18 to 67 years [6]. Intracranial and orbital cavernous hemangiomas in children, especially in infants, are rare [4].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of cerebral cavernous malformations in children is estimated to be between 0.37% and 0.53% [7]. Multiple lesions in a single orbital cavity or simultaneously occurring in both orbits have been reported, while a familial form of orbital cavernous angiomas have also been described [6,8]. The incidence of familial cerebral cases has been estimated to be close to 20% in the literature, and the pattern of inheritance is consistent with an autosomal dominant mode with incomplete clinical penetration and possible de novo mutation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although the significance of steroid receptors in mesenchymal tumors is unclear, it has been suggested that the growth of some of these tumors may be hormone dependent [14,48]. Cases of hemangioma [8, 12,27,33,34,37,39] and angioleiomyoma [22] in which pain presented or increased in intensity during pregnancy or in the course of the menstrual cycle have been reported in several sites, one of which is the orbit [24,25,51].…”
Section: Introductionmentioning
confidence: 97%
“…Orbital cavernous hemangiomas (OCH) are lesions of middle age (mean age at onset of symptoms is 40 years), mainly affecting women [1,5,20,24,31,40]. They constitute 7-16% of orbital lesions according to different authors and have a typical clinical presentation characterized by slowly developing proptosis, diplopia, reduction of visual acuity and restriction of the visual field [5,20,31].…”
Section: Introductionmentioning
confidence: 99%
“…1,3,6,11,19,24) Orbital CHs account for 7-16% of orbital lesions and the typical clinical presentation is characterized by slowly developing proptosis, diplopia, reduction of visual acuity, and restriction of the visual field. 3,6,19) These findings suggest that orbital CH grows slowly.…”
Section: Introductionmentioning
confidence: 99%